LANGUAGE CRIMES IN ENGLISH LANGUAGE (Web of Teachers: Inderscience Research, 2024)
The article explores the semantic and structural characteristics of language crimes in English through the lens of structural linguistics methods. The analysis is based on the role these elements play within the linguistic system, with a focus on various linguistic relationships among the terms that represent language crimes. Crimes committed through language are categorized into two main types based on their targets: those directed at individuals and those aimed at property. Components within this paradigm can belong to multiple fields simultaneously. The study highlights the contradictions within elements belonging to the same paradigm, examining both their general and specific characteristics.